Characterization and functional evaluation of JS207, a novel bispecific antibody against human PD-1 and VEGFA - Lin, Shihua; Hong, Min; Zhang, Jing; Zhao, Wenting; Li, Ke; Wu, Chun; Yang, Qiuyun; Xiao, Yi; Huang, Lanqing; Wang, Jing; Jia, Aijuan; Wang, Xujia; et al. (Frontiers in Immunology, 2025)
IntroductionCancer immunotherapy has been revolutionized by targeting PD-1 to restore antitumor T-cell activity and blocking VEGF to attenuate immunosuppressive tumor angiogenesis. While combining PD-1 and VEGF inhibition has shown promise in enhancing antitumor responses, co-administration of two or more monoclonal antibodies face several challenges, including distinct pharmacokinetics, complex dosing, and toxicity. A bispecific antibody (BsAb) targeting both PD-1 and VEGF pathways could overcome these limitations by enabling simultaneous, localized blockades of PD-1 and VEGF signaling within the tumor microenvironment (TME) as both PD-1 and VEGF are usually co-expressed in the TME.MethodsHere, we describe the in vitro characterization, functional and preclinical evaluation of JS207, a novel BsAb targeting PD-1 and VEGFA with high antigen binding affinity. JS207 matched or surpassed the activity of benchmarks antibodies in several in vitro binding assessments, T cell activation, VEGF signaling inhibition, cytokines (IL-2 and IFN-γ) release.ResultsJS207 showed significant anti-tumor efficacy in mouse MC38 colon cancer model and A375 melanoma tumor model. Investigation into the mechanism of action revealed that VEGFA could significantly promote JS207’s antigen binding activity, T cell activation potency, and internalization of cell surface PD-1. In vivo results demonstrated that JS207 was well-tolerated and presented remarkable anti-tumor efficacy. In addition, JS207 showed enhanced thermal stability as evidenced by retained potency under heat stress, a critical factor for CMC (Chemistry, manufacturing and control) manufacture, storage and drug shelf life.ConclusionJS207 is a promising therapeutic candidate that may address unmet clinical needs in cancer immunotherapy.